Are quartz LPOs predictably oriented with respect to the shear zone boundary?: A test from the Alpine Fault mylonites, New Zealand. (18th March 2016) - Little, Timothy A.; Prior, David J.; Toy, Virginia G.
Abstract: The Alpine fault self‐exhumes its own ductile shear zone roots and has a known slip kinematics. Within ∼1 km of the fault, the mylonitic foliation is subparallel to the boundary of the amphibolite‐facies ductile shear zone in which it formed. Using EBSD, we analyzed quartz Lattice Preferred Orientations [LPOs) of mylonites along a central part of the Alpine Fault. All LPOs feature a strongest girdle of [c]‐axes that is forward‐inclined ∼28 ± 4° away from the pole to the fault. A maximum of axes is inclined at the same angle relative the fault. The [c]‐axis girdle is perpendicular to extensional (C') shear bands and the maximum is parallel to their slip direction. [c]‐axis girdles do not form perpendicular to the SZB. Schmid factor analysis suggests that σ1 was arranged at 60–80° to the Alpine Fault. These observations indicate ductile transpression in the shear zone. The inclined arrangement of [c]‐axis girdles, axes, and C' planes relative to the fault can be explained by their alignment relative to planes of maximum shear‐strain‐rate in a general shear zone, a significant new insight regarding shear zones and how LPO fabrics may generally develop within them. For the Alpine mylonite zone, our data imply a kinematic vorticity number (Wk) of ∼0.7 to ∼0.85. Inversions of seismic focal mechanisms in the brittle crust of the Southern Alps indicate that σ1 is oriented ∼60° to the Alpine Fault; that shear bands form at ∼30° to this direction, and that σ2 and σ3 flip positions between the brittle and ductile parts of the crust. Key Points: Quartz [c]‐axis girdles are 90° to shear bands and maxima parallel to C' slip In transpression, [c]‐axis girdles are not 90° to shear zone boundary Geometry of quartz LPOs and C' bands may be controlled by maximum shear strain rate not SZB